2021
DOI: 10.3390/cells10102524
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of the Novel Tumor Suppressor Role of FOCAD/miR-491-5p to Inhibit Cancer Stemness, Drug Resistance and Metastasis via Regulating RABIF/MMP Signaling in Triple Negative Breast Cancer

Abstract: Triple negative breast cancer (TNBC) possesses poor prognosis mainly due to development of chemoresistance and lack of effective endocrine or targeted therapies. MiR-491-5p has been found to play a tumor suppressor role in many cancers including breast cancer. However, the precise role of miR-491-5p in TNBC has never been elucidated. In this study, we reported the novel tumor suppressor function of FOCAD/miR-491-5p in TNBC. High expression of miR-491-5p was found to be associated with better overall survival i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Targeting JMJD2B is one way that miR-491-5p has been shown to have an antitumor impact in ERα-breast cancer ( 35 ), while targeting this gene by frog oviduct protein hydrolyzate (ORPH) has been shown to increase metastasis in gastric cancer. HCC growth, metastasis, and glycolysis are all slowed by the miR-491-5p/PKM2 axis ( 36 ), and the discovery of the FOCAD/miR-491-5p axis has been shown to reduce cancer stemness, drug resistance, and the development of metastases ( 37 ). The interaction between linc01615 and miR-491-5p regulates the survival and metastasis of colorectal cancer cells ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Targeting JMJD2B is one way that miR-491-5p has been shown to have an antitumor impact in ERα-breast cancer ( 35 ), while targeting this gene by frog oviduct protein hydrolyzate (ORPH) has been shown to increase metastasis in gastric cancer. HCC growth, metastasis, and glycolysis are all slowed by the miR-491-5p/PKM2 axis ( 36 ), and the discovery of the FOCAD/miR-491-5p axis has been shown to reduce cancer stemness, drug resistance, and the development of metastases ( 37 ). The interaction between linc01615 and miR-491-5p regulates the survival and metastasis of colorectal cancer cells ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…DUSP6 is an oncogenic factor in melanoma, and DUSP4 can play its part in the survival and growth of melanoma cells by inhibiting the DUSP6 expression. Increased RABIF expression in breast and triple negative breast cancer patients is related to poorer outcome and considered a potential bioprognostic marker ( 37 ). MMP7 is a stromal lysin protein playing important roles in immunity, apoptosis, angiogenesis, and coagulation and is highly expressed in cancers of various types, including gastric cancer, uveal melanoma, and colon cancer, resulting in infiltration and metastasis of tumor cells ( 38 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…One study revealed that increased C1QA expression was significantly related to a better prognosis in breast cancer ( 41 ). MiR-491-5p was reported to directly targeting RABIF to downregulate cell invasion, metastasis, and drug resistance in triple negative breast cancer ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that the expression of enzymes associated with glycolysis in TNBC resistant TME also has obvious individual differences from other tumors, such as 6‐phosphogluconate dehydrogenase (Luo et al, 2022; Xu, Ren, & Cheng, 2023), enolase (Ma, Zhao, Zhang, et al, 2022). In addition, MMPs are also thought to be associated with TNBC resistance (Huang et al, 2021). Meanwhile, ABC transporter, mutations in DNA repair enzymes, drug targets mutation, and GSH S‐transferase which is considered to be another potential way to improve the drug resistance (Marra et al, 2020; Sharmin et al, 2021).…”
Section: The Features Of the Tme In Tnbcmentioning
confidence: 99%